Transformasi Pelayanan Digital di Tingkat Kecamatan: Studi Efektifitas layanan MyBCA pada Nasabah Bank BCA KCP Ponorogo Cokroaminoto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe and analyze the effectiveness of digital service transformation through the myBCA ecosystem at Bank BCA KCP Ponorogo Cokroaminoto from the perspective of Public Administration. The paradigm shift from the Old Public Administration (OPA) to the New Public Service (NPS) requires service institutions to place citizens as the main subjects through the principles of transparency, accountability, and respect for public dignity. This study uses a descriptive qualitative approach with in-depth interview techniques, passive participatory observation, and documentation. Informants were selected by purposive sampling, including branch management, frontline officers (Customer Service and Teller), and customers. The results of the study show that the transformation towards the myBCA ecosystem has succeeded in significantly improving service efficiency through the transfer of routine administrative processes from bank counters to customer self-service. Features such as Single ID allow for flexible multi-account management, especially for businesses with high mobility in the Cokroaminoto area. This process reflects debureaucratizing practices that encourage frontline officers to focus on value-added consultative services that demand empathy and analysis. The success of this digital adaptation is supported by the synergy between the quality of e-service and the responsiveness of human resources. Although myBCA offers ease of use and reliability of the system, the role of officers as digital educators remains essential in bridging the technology literacy gap. The responsiveness and digital empathy shown by the officers increases public trust and ensures access to professional human support. In line with Law No. 25 of 2009 concerning Public Services, transparency and real-time information through myBCA strengthens institutional legitimacy. Thus, the effectiveness of digital services at KCP Ponorogo is determined by the balance between a reliable digital system and responsive personnel.